2015
DOI: 10.1038/nchem.2349
|View full text |Cite
|
Sign up to set email alerts
|

Co-assembly, spatiotemporal control and morphogenesis of a hybrid protein–peptide system

Abstract: ature uses self-assembly to create a widespread variety of complex structures with elaborate geometries and outstanding properties 1 such as hierarchical order, adaptability, selfhealing and bioactivity. Developing new bioinspired processes based on dynamic self-assembly could facilitate the fabrication of synthetic three-dimensional (3D) materials with enhanced complexity, dynamic properties and functionality 2 . Proteins are particularly attractive building blocks because of their versatility and biofunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
185
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 151 publications
(193 citation statements)
references
References 42 publications
7
185
1
Order By: Relevance
“…Zeta potential ( ) measurements confirmed that both components xanthan and chitosan oligomers have opposite charge and hence, they are able to co-assemble by electrostatic interactions. These type of interactions have been shown essential to drive the self-assembly of interfacial systems [2,5,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Zeta potential ( ) measurements confirmed that both components xanthan and chitosan oligomers have opposite charge and hence, they are able to co-assemble by electrostatic interactions. These type of interactions have been shown essential to drive the self-assembly of interfacial systems [2,5,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…1A). This system relies on the conformational modification of the ELR molecules by interacting non-covalently (electrostatic and hydrophobic interactions) with the PA molecules [10]. While the membrane formed is stable in water, a weakening of the system is visible when immersed in ionic solutions (e.g.…”
Section: Membrane Weakening In Physiological Environmentsmentioning
confidence: 99%
“…In this study, we investigated possible exogenous cross-linking strategies (4S-StarPEG, SCM-PEG-SCM, GNP, and GTA) for the en [10]. (C) Turbidity profile showing the effect of ionic environments on the molecular interaction between ELR and PA after incubation in physiological environment at 4°C and 40°C, respectively.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations